Evaluation of the possibility of Spirulina Spirulina platensis culture in the deep aquifer well, Seistan, Southeastern Iran - Abdolali Rahdari; Ali Khosravanizadeh; Sahel Pakzad Toochaei; Roghayeh Karami (تغذیه آبزیان)
Introduction: Nowadays, Spirulina algae is considered as a food supplement and even a healthy and useful food for human and is available in different forms such as powder, tablets, chips, etc. In addition to human consumption, Spirulina is used in aquaculture for feeding the larval stages of crustaceans and some other types of aquatic animals, to prepare livestock and poultry feed, and for cosmetic and industrial purposes. This study was carried out to evaluate the water capacity of the country's first deep aquifer well located in the Seistan region for the cultivation of Spirulina platensis.Materials and methods: Six treatments including deep aquifer well water with high salinity of 25, 12.5, and 5 ppt (Seistan deep aquifer well without changing salinity, deep water diluted with distilled water to 12.5 ppt salinity and 5 ppt) and tap water with high salinity of 25, 12.5 and 5 (prepared from Urmia Lake salt) were prepared. Spirulina algae was cultivated under standard conditions including temperature 30 ± 2 °C, light 37 µmol/m2/s; 16 hours light and 8 hours darkness for 21 days. At the end of the test period, the growth indicators and pigment concentration of the produced algae were measured, and by comparing the data obtained in different treatments, the ability of deep aquifer well water to grow Spirulina algae was determined.Results and discussion: The results showed that the highest biomass was obtained in the treatment of tap water and Urmia salt (2.91 ± 0.14 g/L) and the growth rate in the treatments containing deep aquifer water was lower than the other treatments.Conclusions: The cultivation of Spirulina in the water of deep well (No. 1 Seistan) has a low efficiency compared to tap water, and it is necessary to modify and change its composition in some way so that Spirulina can be cultivated in with proper efficiency. Conflicts of interest: Authors have no conflict of interest to declare for the publication of the present work. Acknowledgments: The authors thank the Research Institute of Zabol for funding this study (PR-RIOZ-1401-9571-1).